Clinical value of FNA puncture feeling in the diagnosis of non-diagnostic and indeterminate thyroid nodules - Wu, Jintao; Li, Yingying; Zhang, Mingbo (Frontiers in Endocrinology, 2022)
Objective The aim of this study was to explore the clinical diagnostic value of puncture feeling during fine-needle aspiration (FNA) for non-diagnostic and indeterminate thyroid nodules. Methods A retrospective analysis was performed on 176 patients (196 nodules) diagnosed with Bethesda I or III by FNA cytology at the ultrasound department of our hospital between January 2017 and January 2020. Comparisons were made on the differences in puncture feeling (including stiffness and grittiness) between benign and malignant thyroid nodules, and their diagnostic performance was analyzed. Results There were significant differences between benign and malignant nodules with respect to the puncture stiffness and puncture grittiness (P < 0.001). The presence of a hard stiffness and grittiness demonstrated comparable levels of diagnostic performance for malignant thyroid nodules, with sensitivities, specificities, accuracies, positive predictive values, and negative predicative values of 55.56% and 63.89%, 87.10% and 78.22%, 75.51% and 72.96%, 71.43% and 63.01%, and 77.14% and 78.86%, respectively. The diagnostic performance was most optimal in the presence of at least one puncture feeling (area under the receiver operating characteristic curve: 0.771), exhibiting a sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of 79.17%, 75.00%, 75.00%, 76.53%, 64.77%, and 86.11%, respectively. Conclusions Puncture feeling adds clinical value in the diagnosis of thyroid nodules with indeterminate FNA findings.